(Re)Construction of Child-Friendly Schools to Prevent Bullying - Siany Indria Liestyasari (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This study aims to analyze how the construction and reconstruction of the implementation of Child-Friendy School (CFS) policies in bullying prevention are unique in each school by using the theoretical approach of behaviorism and social constructivism. This study uses a case study method with a qualitative approach involving three senior high schools located in Surakarta, Indonesia. The informants were teachers, principals, and students in child-friendly schools. The research instrument used unstructured interviews and school observations as well as focus group discussions with policymakers related to child-friendly schools. Data analysis techniques in this study were carried out interactively through the stages of data reduction, data presentation, and drawing conclusions. The results show that the implementation of CFS with a behavioristic pattern needs to be strengthened with a pattern of social constructivism because it is not significant enough to institutionalize CFS in schools, especially in efforts to prevent bullying. The recommendations submitted are conducting a needs analysis according to the conditions of each school by stakeholders, building student character through the student literacy humanity movement, and rootdays activities so that students have experience, thought construction and tolerance attitudes towards diversity. The above makes child-friendly schools can be a strategy to prevent bullying.